Decline processes in technological innovation systems: Lessons from energy technologies - Bento, N.; Nuñez-Jimenez, A.; Kittner, N. (Research Policy, 2025)
Technology decline is gaining attention in sustainability transitions because it can accelerate the adoption of sustainable alternatives and mitigate the lingering impacts of polluting technologies. However, a systematic analysis of the processes driving the decline of established technologies remains absent. This paper addresses this gap by introducing the concept of “decline functions,” inspired by the functional analysis of technological innovation systems (TIS). While traditional TIS functions make emerging systems thrive, decline functions contribute to the unravelling of faltering systems. Four decline functions are suggested: delegitimation, guidance toward exit, market decline, and resource demobilization. These functions are applied to four energy-technology cases: incandescent light bulbs, oil-based heating, nuclear power and internal combustion engine cars. Data were collected through a directed literature review. Our analysis reveals that all four decline functions were present and played important roles across the cases. These functions offer a systematic framework for analyzing and comparing cases of declining TIS and can provide actionable insights for policymakers to accelerate sustainability transitions.